Integrated Reporting: Corporate Strategy Towards Achieving Sustainable Development SDGs - Rumanintya Putri; Desak Nyoman Sri Werastuti; Ernany Dwi Astuty; Aulia Fatimah Khairunnisa; Eko Wahyono; Ni Luh Apriani (Apollo: Journal of Tourism and Business, 2023)
This article aims to explain the implementation of a sustainable development strategy in the enterprise. The organization of the company is not only to meet the needs of the government, but also for the long-term interests of the company. The research method used is through a qualitative analysis of the variables of earnings growth per share and company share price in financial services institutions, issuers and the corporate sector of the company. Basic concepts are also used and additional data is used to support each given argument. The fundamental flaws of the integrated reporting system are then analyzed, making comparisons between companies difficult. We also assess how well a company implements its Sustainability Strategy (SDGs) using common metrics that can be used by parties outside and within the business